Facilitating Empowerment and Self-Determination Through Participatory Action Research: Findings From the National Empowerment Project. Issue 1 (20th March 2017) - Dudgeon, Pat; Scrine, Clair; Cox, Adele; Walker, Roz
The National Empowerment Project (NEP) is an innovative Aboriginal-led community-based project. Since 2012, it has been working with communities in 11 sites across Australia to develop a culturally appropriate health promotion and primary prevention intervention strategy to reduce the high rates of psychological distress and suicide among Aboriginal and Torres Strait Islander peoples. The NEP is built around the use of localized participatory action research (PAR) processes to support communities to identify key factors negatively impacting on their lives as well as strategies for promoting well-being and building resilience. This article details the application of the PAR approach by the NEP Aboriginal community-based researchers. It provides some unique insights into how PAR facilitated communities to have a voice and the ways in which it supported important change processes at both an individual and a community level.